The efficacy and side effects of liposomal doxorubicin-based therapy and epirubicin-based therapy for breast cancer patients: a meta-analysis - DENG Lang; XIONG Dayan; TIAN Jiashuo; DING Jinfeng; TANG Siyuan; LIU Wei (Guangxi Yike Daxue xuebao)
Objective To conduct a meta-analysis to explore the specific efficacy and side effects of liposomal doxorubicin (LD) and epirubicin (E)-based therapies in breast cancer patients. Methods We searched 6 databases including PubMed, Embase, CNKI, Wanfang Data, Web of Science, and the Cochrane Library, and adopted retrospective studies and randomized clinical trials (RCTs) to compare the efficacy and side effects during LD and Ebased therapies. Cochrane criteria were followed, and the RevMan 5.3 software was used to analyze the pathological complete response rate, as well as the side effects of the trials such as cardiotoxicity, immunotoxicity, hematotoxicity and neurotoxicity. The odds ratios (OR) and 95% confidence intervals (95% CI) were used to present the results. Results In total, we analyzed the results from 3, 597 patients in 5 RCTs and 16 retrospective studies. The meta-analysis results showed that the LD-based therapy had better performance than the E-based therapy in pathological complete response rate (OR=1.31), incidence of cardiotoxic events (OR=0.40) and incidence of hematotoxic events (OR=0.59) (P < 0.05). However, LD-based therapy showed significantly higher immunotoxicity (OR=2.52) and neurotoxicity (OR=0.59) (P < 0.05). Conclusion Compared with E-based therapy, LD-based therapy is generally more suitable for breast cancer patients. However, for patients with a burden of immune system and nervous system diseases or other related contraindications, careful selection should be made.